PENGARUH PROMOSI, KUALITAS PRODUK DAN BRAND IMAGE TERHADAP MINAT BELI HANDPHONE MEREK NOKIA - Italia, Italia; Islamuddin, Islamuddin (Yayasan Insani Mandiri Santani, 2021)
This study entitled the effect of Promotion, Product Quality, and Brand Image on Buying Interest for Nokia Brand Mobile (Case Study on Nokia Consumers in Bengkulu City).This study study aimed to know the simultaneous effect between Promotion, Product Quality and Brand Image on Purchase Intention for Nokia Brand Mobile Phones. The object of this study was Nokia consumers in Bengkulu City, using purposive sampling method. The number of respondents in this study were 96 people. The data collection method employed a questionnaire. To analyze the data, the study used multiple linear regression data analysis techniques. Based on the results of multiple linear regression, the form of regression equation is Y = 4,648 + 0.384 (X_1) + 0.571 (X2) + 0.421 (X3). The study results and hypotheses indicated that Promotion (sig Î± = 0.041 <0.050), Product Quality (sig Î± = 0.004 <0.050), and Brand Image (sig Î± = 0.000 <0.050). Simultaneously, it has a positive and significant effect on Buying Interest. Regarding the three variables Promotion, Product Quality, and Brand Image have an influence on Buying Interest in Nokia consumers in Bengkulu CityKeywords: promotion, product quality, brand image, purchase interest